2017
DOI: 10.1111/jcpe.12744
|View full text |Cite
|
Sign up to set email alerts
|

Effect of surgical periodontal treatment associated to antimicrobial photodynamic therapy on chronic periodontitis: A randomized controlled clinical trial

Abstract: A single episode of aPDT used in adjunct to open flap debridement of the root surface in the surgical treatment of SCP: i) significantly improved clinical periodontal parameters; ii) eliminates periodontal pathogens of the red complex more effectively (NCT02734784).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
52
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(53 citation statements)
references
References 61 publications
1
52
0
Order By: Relevance
“…Even though there are important studies on the association of SRP procedures with multiple sessions of aPDT, there is a paucity of studies that associate this therapeutic method with the surgical treatment of periodontal disease. Martins et al . associated a single intraoperative session of aPDT with the surgical treatment of SCP and observed a decrease in PD at 90 postoperative days when compared with baseline (with an average of 2.30 mm in the CG and 2.93 mm in the TG).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Even though there are important studies on the association of SRP procedures with multiple sessions of aPDT, there is a paucity of studies that associate this therapeutic method with the surgical treatment of periodontal disease. Martins et al . associated a single intraoperative session of aPDT with the surgical treatment of SCP and observed a decrease in PD at 90 postoperative days when compared with baseline (with an average of 2.30 mm in the CG and 2.93 mm in the TG).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies of aPDT associated with non‐surgical therapy for periodontal treatment are controversial . However, only one study in the literature presents the association of a single session of aPDT with a surgical periodontal treatment . Thus far, multiple sessions of aPDT have not been evaluated as an adjunctive therapy for surgical periodontal treatment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Martins et al. () in their study did weekly sessions of scaling and root planning (SRP) using both hand instruments and ultrasonic device 30 days after last session of SRP. The test group received flap debridement and aPDT protocol consisting of application of phenothiazine chloride solution (10 mg/ml) and diode laser (660 nm, 28 mW/cm 2 , 10 s per site and 2.79 J/cm 2 per tooth).…”
Section: Photodynamic Therapy In Oral Diseasesmentioning
confidence: 99%
“…In contrast, Martins et al. () used aPDT (phenothiazine chloride, 10 mg/ml, 660 nm diode laser, 28 mW/cm 2 , 10 s per site, 2.79 J/cm 2 per tooth) in a split‐mouth study in severe chronic periodontitis treated with surgical periodontal treatments. Results in this study demonstrated both procedures significantly improved clinical outcomes and reduced subgingival bacteria analyzed 90 days after treatment.…”
Section: Photodynamic Therapy In Oral Diseasesmentioning
confidence: 99%